The Family Parenting Influenced Adolescent Brawls Behavior - Heni Nurhaeni; Dinarti Dinarti; Dwi Priharti (Institute of Advanced Engineering and Science, 2016)
There are four types of parenting: democratic, authoritarian, permissive, and ignored, which would affect the character of the child. But family upbringing itself influenced education, norms/cultural, environmental, social, economic and belongs to the family members. quasi-experimental study through questionnaires, observation, deep interview, and interventions against high school Students, Peers, Teachers (BK), and their Parents/Family have been conducted through a random sampling of 108 respondents in four high school set. The result met the test paired T test statistical significance level 0 and T test result of 0.05 shows that the two variables p-value of p=0.00000. Correlation tests showed that there is a relationship between two variables at-0616. This sign (-) means that the test results are negative correlation. Can be seen if the correlation between the two variables is quite high between 0.50 to 1.0 can be concluded that the direction of the relationship between the two variables is negative. These results can be displayed from